Implementation of Role-Playing Active Learning to Increase Student Learning Outcomes on the Digestive System Materials - Effendi, Dailan (International Journal of Education Research and Development, 2021)
Implementation of Role Playing Active Learning to Improve Student Learning Outcomes on Digestive System Materials VIII grade of Junior High School 6 Rejang Lebong Regency Academic Year 2020/2021The number of students who get the value of biology subjects below minimum completeness is due to one of them because the learning process so far has not involved students actively, therefore this study aims to determine the improvement of biology learning outcomes, especially on the subject matter of the digestive system in humans by applying the role playing method. . This research is a Classroom Action Research which involves four components, namely: Planning (plans), Action (action), Observation (observation), Reflection (reflection). The subjects in this study were students of class 8.1, totaling 43 students. This study uses a classroom action research (CAR) design which consists of two cycles. From the results of the study obtained: The results of the test (cognitive domain) in the first cycle, the average grade of 65.5 with 65% completeness of learning, the lowest score of 40 and the highest score of 90, students who completed learning individually as many as 28 students and 15 students who had not. finished. In the second cycle the average test score of the class reached 71.5 with class learning completeness of 87.5%, the lowest score was 45 and the highest score was 95, 38 students who completed individual studies and 5 students who had not completed.